Electrospray ionization mass Spectrometry of a novel family of complexes in which various nitroso compounds are stabilized via coordination to [IrCl5]2- - Escola, Natalia (2007)
Electrospray ionization mass spectrometry (ESI-MS) and tandem mass spectrometry (ESI-MS/MS) data of a unique family of complexes of nitroso compounds coordinated to pentachloroiridate(III), [Cl5IrN(O)XR]2- (X = NH, S, CH and R = alkyl, aryl) are presented. These novel complexes are obtained by nucleophilic attack of primary amines, thiols. and alkenes to the coordinated nitrosyl. Despite their lability and low volatility, MS analysis of complexes of the type MN(O)X was done for the first time, complementing other spectroscopic techniques. The intrinsic dissociation chemistry of the gaseous diagnostic ions was studied via ESI-MS/MS and found to be very useful to confirm the proposed connectivities of the parent complexes. In particular, ESI-MS of their solutions allows the detection of series of diagnostic ions, mainly, [M − Cl]-, [M + K]-, [M − NO]-•, and [M − Cl + AcN]- (AcN = acetonitrile), which confirmed the identity of the analyzed complexes to be M = [Cl5IrN(O)XR]2-. Major fragments were formed by losses of NO or N(O)XR. ESI-MS and ESI-MS/MS measurements are therefore shown to be the proper techniques to complement the spectroscopic characterization of this important class of nitroso complexes. An interesting rearrangement that does not take place in solution was observed in the gaseous phase, and a plausible mechanism is discussed.